PENGUATAN KAPASITAS PRANATA LOKAL DALAM PENANGANAN PRE DAN POST PARTUM PADA IBU HAMIL UNTUK MENGURANGI DAMPAK KESEHATAN AKIBAT TEKANAN SOSIAL DAN EKONOMI DI KECAMATAN MANYAR KABUPATEN GRESIK (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This community service activity targets local institutions as agents of change in the community. It is hoped that local institutions can socialize and even move the community to be critical of the problems often faced by pre- and post-partum mothers. The methods used in this community service are socialization, discussion, question and answer, sharing experiences which are carried out through three stages, namely preparation, implementation and evaluation. The result of the community service implementation is the critical awareness of the participants as seen from the ability of participants to be able to identify problems in their environment related to pre- and post-partum maternal health problems such as identifying forms of bullying. Participants were also able to identify factors causing health problems faced by pre- and postpartum mothers such as early marriage to how cultural hegemony or myths developed in society.